Exosomal encapsulation of a steviol derivative SD9 to overcome TRAIL resistance as a highly effective therapy against lung cancer - Quanjiang Li; Yufeng Xie; Wanting Zhang; Jun Peng; Zhujie Deng; Rui Tian; Xiubin Kuang; Bin Xie; Chen Huang; Yu Zhao; Zhengqiang Yuan (Cancer Nanotechnology)
Abstract Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is a promising pro-apoptotic factor. However, it has showed very limited efficacies due to low bioavailability and common drug resistance in cancers. Extracellular vesicle delivery of TRAIL (EV-T) has significantly improved the activity and the combination of EV-T with some intrinsic apoptosis-inducing chemical compounds showed further strikingly augmented apoptosis induction in cancers. Previously we synthesized a steviol derivative 9# (SD9) that induced intrinsic apoptosis in cancer cells. However, it has never been examined if SD9 collaborates with EV-T to trigger synergistic apoptosis-induction in cancer cells. Herein, we propose that SD9 may be loaded into EV-T to sensitize TRAIL response for a synergistic anti-cancer therapy. First, TRAIL-transduced mesenchymal stem cells (MSCs) were used to produce EV-Ts. Then SD9 was encapsulated into EV-Ts to prepare the complexed nanodrug SD9@EV-T. The encapsulation of SD9 resulted in not only increased cellular delivery rate, sustained drug release and improved pharmacodynamics, but also synergistically and selectively augmented apoptosis induction in 8 various cancer cell lines, but not in normal cells. The related molecular mechanisms are involved in the concomitant upregulation of DR5 and suppression of anti-apoptotic factors including cFLIP, MCL-1, BCL-2 and IAPs and the NF-kappaB pathway. Additionally, SD9@EV-T was in vivo tested for anti-cancer therapeutic efficacy in a subcutaneous A549 xenograft lung tumor model. The SD9@EV-T therapy demonstrated strikingly promoted efficacy than the SD9 alone treatment, and no evident adverse drug events (ADEs) were observed. In conclusion, the SD9@EV-T nanodrug potentially constitutes a novel and highly effective anti-cancer therapy.